Selected Problems in Translation of Culture-bound Elements in Marek Hłasko’s “Beautiful Twentysomethings” - Kołodziejczyk, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Artykuł analizuje tłumaczenie wybranych elementów kulturowych w „Pięknych dwudziestoletnich” Marka Hłaski w odwołaniu do teorii Olgierda Wojtasiewicza, Krzysztofa Hejwowskiego i Petera Newmarka. Składa się z czterech części, w których, kolejno, omówione zostały przekłady elementów kulturowych związanych z rzeczywistością komunizmu w Polsce, aluzji kulturowych i literackich oraz pochodzące od tłumacza poprawki wyrażeń anglojęzycznych w utworze. Na końcu sformułowane zostały syntetyczne wnioski z analiz.

The subject of the article is an analysis of the translation of selected culture-bound terms in “Beautiful Twentysomethings” by Marek Hłasko. The study is based on theoretical assumptions by Olgierd Wojtasiewicz, Krzysztof Hejwowski and Peter Newmark. The study is divided into four parts. The first one discusses translations of cultural elements relating to the Communist realm in Poland. The second focuses on the ways knowledge of the cultural allusions has been transmitted. The third one presents the analysis of the ways literary allusions were translated. The fourth one presents the translator’s amendments of Marek Hłasko’s English expressions. The conclusions complement the study.
Wybrane problemy tłumaczenia elementów kulturowych w przekładzie „Pięknych dwudziestoletnich” Marka Hłaski
Keywords: elementy kulturowe w przekładzie; aluzje literackie; Marek Hłasko; Ross Ufberg; culture-bound terms in translation; literary allusions